Penggunaan Ekstrak Tomat untuk Peremajaan L. acidophilus FNCC sebagai Media Alternatif pada Penyiapan Starter Fermentasi - Ari Surya Sukarno; Widodo; Satyaguna Rakhmatulloh; Nurliyani; Endang Wahyuni (LPPM Perjuangan University of Tasikmalaya, 2023)
Lactic acid bacteria are a milk fermentation starter that relies on MRS media as a source of nutrition for culture refreshment. This study aims to determine the growth and viability of L. acidophilus FNCC on tomato extract media as an alternative medium. Tomato extract was obtained by sterilization at 121°C with a pressure of 15 Psi for 15 minutes, and the liquid from the tomatoes was collected. L. acidophilus FNCC was grown in tomato extract medium and liquid MRS as a control for 12 hours at 37°C. The amount of biomass growth was measured at 0, 2, 6, 8, 10, and 12 hours based on the increase in turbidity using an absorbance of λ620. Storage viability was observed for changes in the total number of lactic acid bacteria every week for 28 days. The analysis was repeated three times, and data analysis was carried out using a Randomized Design One Way Annova. Incubation L. acidophilus FNCC for 12 hours resulted in an absorbance value of 1.44 ± 0.02 on MRS media which was higher (P<0.01) than using tomato extract, which only reached 0.04 ± 0.02. The storage viability of L. acidophillus FNCC for 28 days in tomato extract media was maintained with the same amount of log log 8.85 ± 0.58 cfu/mL cfu/mL (P>0.05) with the MRS control medium. Therefore, tomato extract can be used as an alternative medium to grow and store L. acidophilus FNCC for 28 days.